Mahākavi Uḷḷūruṃ Malayāḷasāhityavuṃ - Rāmacandṟan Nāyar, Ke., 1930-; Vēlāyudhanpiḷḷa, Pi. Vi., 1931- (Publications of the Department of Malayalam., 1978)
Commemoration volume for Uḷḷūr Es. Paramēśvarayyar, 1877-1949, Malayalam poet; comprises papers presented at a seminar, Trivandrum, 1977, on the poet's life and works, organized to celebrate his birth centenary.